CLINICAL APPLICATIONS OF CARBAMYLATED HEMOGLOBIN IN RENAL DISEASES - Abdel-Hady Mashahit, Mohamed; Morsy El-Shafeey, Shahira; Sayed El-Toukhy, Hala; Adly Ali, Ragab; AbdelAziz, Hossam; Gamal Ali, Mahmoud (Acta Scientiae et Intellectus, 2024)
Carbamylated hemoglobin is formed by reaction of isocyanate (urea dissocia-tion product) with valine residues of Hb chains. Different studies demonstrated that carbamylated hemoglobin level is increased in patients with renal impairment. This study concluded that carbamylated hemoglobin level significantly correlates with serum creatinine (r=0.411, moderate positive) and urea level (r=0.408, moderate positive) (p<0.001). This correlation may be important in clinical settings makes carbamylated hemoglobin good biomarker for renal impairment, and may reflect severity and duration of renal impairment. We also found that carbamylated hemoglobin level is not affected by the diabetes state of the patient.